2013
DOI: 10.1073/pnas.1302328110
|View full text |Cite
|
Sign up to set email alerts
|

Broader perspective on ecosystem sustainability: Consequences for decision making

Abstract: Although the concept of ecosystem sustainability has a long-term focus, it is often viewed from a static system perspective. Because most ecosystems are dynamic, we explore sustainability assessments from three additional perspectives: resilient systems; systems where tipping points occur; and systems subject to episodic resetting. Whereas foundations of ecosystem resilience originated in ecology, recent discussions have focused on geophysical attributes, and it is recognized that dynamic system components may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
41
0
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 74 publications
0
41
0
4
Order By: Relevance
“…Valuation of these services is critical for public policy (10,11), but many of the services provided by freshwater ecosystems are not monetized (12,13), leaving them overlooked and poorly integrated into decision frameworks (1,3). Water quality of lakes and reservoirs has been degraded by phosphorus (P) pollution, leading to loss of recreation and aesthetic value, decreased lakeshore property values, beach closures, fish kills, harmful blooms of cyanobacteria, and loss of water clarity (14).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Valuation of these services is critical for public policy (10,11), but many of the services provided by freshwater ecosystems are not monetized (12,13), leaving them overlooked and poorly integrated into decision frameworks (1,3). Water quality of lakes and reservoirs has been degraded by phosphorus (P) pollution, leading to loss of recreation and aesthetic value, decreased lakeshore property values, beach closures, fish kills, harmful blooms of cyanobacteria, and loss of water clarity (14).…”
mentioning
confidence: 99%
“…invasive species | ecosystem service | eutrophication | Bythotrephes | Daphnia D espite growing recognition of the importance of ecosystem services (1) and the harm caused to ecosystems by invasive species (2,3), linkages between species invasions and ecosystem services are rarely made (4)(5)(6). Investments in the prevention of species invasions may sustain ecosystem services.…”
mentioning
confidence: 99%
“…The assessment here of the tephra-fall problem has shown that vulnerability exists due to current land use in Iceland and that the underlying risk factors could be reduced. Prevention of tephra-fall events is impossible, but improved ecosystem health could prevent further degradation and move systems away from negative ecosystem tipping points (Sidle et al 2013). Mitigation has been shown to improve ecosystem resilience.…”
Section: Discussionmentioning
confidence: 99%
“…Mitigation has been shown to improve ecosystem resilience. Monitoring improves knowledge on ecosystem status, detects subtle signs of resilience loss (Sidle et al 2013), and suggests improvements. Such monitoring is important to set up in Iceland.…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers have started to establish their own methodologies with a focus more on environmental impacts than resource availability, among which are Mwalyosi [1991], McConnell [1995], Graymore [2005], and Graymore et al [2010]. NRECC methodologies form a different perspective regarding resources and environment which so far includes various organizational elements, such as the carrying capacity of land resources [Cohen, 1995;Gutteridge, 2006;Fairlie, 2007], the carrying capacity of water resources [Falkenmark and Lundqvist, 1998;Peters et al, 2009;Song et al, 2011], the carrying capacity of the environment or environmental capacity [Van Den Bergh, 1993;McConnell, 1995;Graymore et al, 2010], the ecological sustainability index or ecological footprint [Rees, 1992;Barrett and Odum, 2000;Sidle et al, 2013]. These current methodologies are often based on single factor assessment.…”
Section: Supporting Informationmentioning
confidence: 99%